(untitled) (Medico Legal Update, 2020)
The Diabetis is one of the most common chronic disorder across the world and the number of diabetic patients is on the rise .Majority of patients with type 2 diabetics fail to control glycaemia with diet and exercises .Lack of adherence to diabetic medication causes glycemic control and causes and can lead to treatment failure, development of complications and increases mortality. The objectives of the study were to assess the compliance to medications among type 2 diabetic patient and the demographic variables. A non-probability- purposive sampling technique is used to collect data from the samples. The sample size was 60 samples at selected rural community. The research design used in this study is Non experimental, Descriptive Research Design where Morisky Medication Adherence Scales is to determine the level of compliance of medication . The level was assessed by questionnaires. The result shows 1(2%) of sample had low adherence, 12(20%) of the sample had medium adherence, 47(78%) of sample had high adherence. There was significant association between the age, no significant association between other demographic variables.